Examining the reliability and validity of a modified version of the International Physical Activity Questionnaire, long form (IPAQ-LF) in Nigeria: a cross-sectional study - Oyeyemi, Adewale L (BMJ Open, 2014)
OBJECTIVES: To investigate the reliability and an aspect of validity of a modified version of the long International Physical Activity Questionnaire (Hausa IPAQ-LF) in Nigeria. DESIGN: Cross-sectional study, examining the reliability and construct validity of the Hausa IPAQ-LF compared with anthropometric and biological variables. SETTING: Metropolitan Maiduguri, the capital city of Borno State in Nigeria. PARTICIPANTS: 180 Nigerian adults (50% women) with a mean age of 35.6 (SD=10.3) years, recruited from neighbourhoods with diverse socioeconomic status and walkability. OUTCOME MEASURES: Domains (domestic physical activity (PA), occupational PA, leisure-time PA, active transportation and sitting time) and intensities of PA (vigorous, moderate and walking) were measured with the Hausa IPAQ-LF on two different occasions, 8 days apart. Outcomes for construct validity were measured body mass index (BMI), systolic blood pressure (SBP) and diastolic blood pressure (DBP). RESULTS: The Hausa IPAQ-LF demonstrated good test–retest reliability (intraclass correlation coefficient, ICC>75) for total PA (ICC=0.79, 95% CI 0.65 to 0.82), occupational PA (ICC=0.77, 95% CI 0.68 to 0.82), active transportation (ICC=0.82, 95% CI 0.75 to 0.87) and vigorous intensity activities (ICC=0.82, 95% CI 0.76 to 0.87). Reliability was substantially higher for total PA (ICC=0.80), occupational PA (ICC=0.78), leisure-time PA (ICC=0.75) and active transportation (ICC=0.80) in men than in women, but domestic PA (ICC=0.38) and sitting time (ICC=0.71) demonstrated more substantial reliability coefficients in women than in men. For the construct validity, domestic PA was significantly related mainly with SBP (r=−0.27) and DBP (r=−0.17), and leisure-time PA and total PA were significantly related only with SBP (r=−0.16) and BMI (r=−0.29), respectively. Similarly, moderate-intensity PA was mainly related with SBP (r=−0.16, p<0.05) and DBP (r=−0.21, p<0.01), but vigorous-intensity PA was only related with BMI (r=−0.11, p<0.05). CONCLUSIONS: The modified Hausa IPAQ-LF demonstrated sufficient evidence of test–retest reliability and may be valid for assessing context specific PA behaviours of adults in Nigeria.